DEVELOPING STUDENTS’ READING ACHIEVEMENT BY USING THINK-PAIR-SHARE (TPS) - Mustaqim (Language and Education Journal, 2017)
Indonesia has low interest in reading. It indicated that students’ reading achievement were low. As teachers of English, they should work hard to make students love reading and improve their reading achievement. One of the way to improve students’ reading achievement was using Think Pair Share (TPS). The objective of this study was to find out whether or not there was a significant difference between the students who were taught by using TPS and that of those who were not. Quasi-experimental method was used. The samples were two classes of the eleventh-grade students of SMA Negeri 2 Tanjung Raja. The written test of reading was used in order to collect the data. The test was tested to non samples so as to find the reliability of the test. In terms of validity, content validity was used. Based on the comparison between the experimental and control groups which was analyzed using independent sample t-test, it was found that t-obtained (2.054) was higher than t-table (2.021) and p-value (0.046) was less than ᾳ-value (0.05). It indicated that Think Pair Share (TPS) could improve the students’ reading comprehension achievement, especially in answering question easier. Besides, Think Pair Share (TPS) could enhance students’ reading comprehension achievement if the students exposed to do it. In other words, there was a significant difference between the students who were taught by using TPS and that of those who were not